THE USE OF ENERGY MANAGEMENT SYSTEM AT ENTERPRISES AND ORGANIZATIONS OF HOUSING AND COMMUNAL SERVICES ON THE BASIS OF THE REQUIREMENTS STANDARD ISO50001 - Evgeniy I. Beliaev; Iola Y. Kuklite; Polina E. Beliaeva (Вестник Северо-Кавказского федерального университета, 2022)
The possibilities of using the principles of energy management in accordance with the requirements of the international standard ISO50001 to improve management efficiency in housing and communal services. The results of research of problems of housing management for management companies and homeowners, the algorithm for comparative evaluation of energy-saving technologies in the reconstruction of the housing stock.